1999
DOI: 10.1017/s1368980099000282
|View full text |Cite
|
Sign up to set email alerts
|

Public health issues arising from microbiological and labelling quality of foods and supplements containing probiotic microorganisms

Abstract: Objective: To assess the accuracy and helpfulness of labelling on products containing probiotic bacteria. Design and setting: 52 such products -44 from the UK (21 supplements, 15 fermented functional foods, eight 'health-care' products) and eight from continental Europe -have been tested for microbiological content, and results compared to the information available on their labels. Products were stored in the dark at 4ЊC and analysed before their expiry or sell-by date. Careful note was taken of wording on lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(100 citation statements)
references
References 9 publications
3
91
0
4
Order By: Relevance
“…In our study, out of eighty dietary supplement samples tested, nine products showed the presence of coliform, E. coli, Salmonella and Staphylococcus aureus. Hamilton-Miller et al (1999, 2002 reported that out of 30 probiotic suppelmenbts tested, 18 contained species other than those on label indicating poor standard of supplements contrary to the claim. Authors have also reported the presence of potentially pathogenic species such as E. faecium.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, out of eighty dietary supplement samples tested, nine products showed the presence of coliform, E. coli, Salmonella and Staphylococcus aureus. Hamilton-Miller et al (1999, 2002 reported that out of 30 probiotic suppelmenbts tested, 18 contained species other than those on label indicating poor standard of supplements contrary to the claim. Authors have also reported the presence of potentially pathogenic species such as E. faecium.…”
Section: Discussionmentioning
confidence: 99%
“…A polyphasic approach to speciation of lactic acid bacteria was recommended by Vandamme (1996), whereby results of genomic analysis and phenotypic analysis are combined. Phenotypic methods, including analysis of cell wall composition, carbohydrate fermentation (Canganella et al, 1997;Hamilton-Miller, et al, 1999;Chateau et al, 1994), and protein analysis have been used for this purpose (Klein et al, 1998). In this study, we assessed speciation inaccuracies in a collection of commercial and research probiotic lactoba cilli and bifidobacteria using carbohydrate fermentation, partial 16S rDNA sequencing, and cellular fatty acid methyl ester methods, and determined the taxonomic relationship of these probiotic strains using these methods.…”
Section: Introductionmentioning
confidence: 99%
“…The optimism related with probiotics is, however, counter-balanced by skepticism as many "probiotic" products in the market are untrustworthy in content and unproven clinically (Hughes and Hillier, 1990;Hamilton-Miller et al, 1999;Zhonget al, 1998). Many probiotic strains used for several decades for their safety and efficiency and are therefore, safe to use Adams and Marteau, 1995).…”
Section: Probiotic Organismmentioning
confidence: 99%